Disseminated Histoplasmosis with Oral Manifestation in an Immunocompetent Patient - Debopriya Chatterjee; Aishwarya Chatterjee; Manoj Agarwal; Meetu Mathur; Setu Mathur; R. Mallikarjun; Subrata Banerjee (Case Reports in Dentistry)
A case of disseminated histoplasmosis (DH) in a 60-year-old female patient is reported from Jaipur, Rajasthan, India. The patient presented with multiple papules on the skin surrounding the lips, face, torso, trunk, and back. She also complained of growth in the palate. Histoplasmosis was confirmed by biopsy and histopathology of skin and palatal lesions. This case report highlights the presenting features and occurrence of histoplasmosis in nonendemic region in India.